Pre-eclampsia through the eyes of the obstetrician and anesthesiologist. (November 2019) - Siddiqui, M.M.; Banayan, J.M.; Hofer, J.E.
Highlights: Despite vigilant surveillance, the incidence of pre-eclampsia is increasing. Early diagnosis and treatment of severe hypertension limits complications. Transthoracic echocardiography and lung ultrasound can guide intrapartum therapy. Pre-eclampsia can lead to long-term cardiovascular complications. A peripartum multidisciplinary approach may optimize outcomes. Abstract: Due to the high risk of morbidity and mortality from unrecognized and untreated pre-eclampsia, clinicians should have a high index of suspicion to evaluate, treat and monitor patients presenting with signs concerning for pre-eclampsia. Early blood pressure management and seizure prophylaxis during labor are critical for maternal safety. Intrapartum, special anesthetic considerations should be employed to ensure the safety of the parturient and fetus. Patients who have pre-eclampsia should be aware that they are at high risk for the future development of cardiovascular disease.